2004
DOI: 10.1238/physica.topical.113a00141
|View full text |Cite
|
Sign up to set email alerts
|

On the Observation of Charged Dust in the Tropical Mesosphere

Abstract: The very first instrument launched to study charged dust in the tropical mesosphere detected a thick layer of fine dust (radius ≈10 nm) near the mesopause. While the dust in the thinner lower part of the layer carried a negative charge the dust in the thicker upper part carried a positive charge (Gelinas, et al., 1998). While the negative charge on the dust was expected, the positive charge was not because the observation was half hour after local astronomical sunset. The observers sought to resolve the proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 4 publications
0
27
0
Order By: Relevance
“…It was also pointed out that values of W ranging from ∼2.3 eV to lower, were used by several authors attempting to explain positive grain potentials observed in the summer polar mesosphere, in terms of photoemission, which also requires a small value of W . Further, as pointed out earlier, Mendis et al [2004] provided an explanation for the observation of nanometer‐sized, positively charged grains observed in the night side tropical mesosphere [ Gelinas et al , 1998], in terms of recondensation of the positively charged spray from an ablating positively charged micrometeoroid traversing that region. This too required a low value of W ≈ 2 eV.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…It was also pointed out that values of W ranging from ∼2.3 eV to lower, were used by several authors attempting to explain positive grain potentials observed in the summer polar mesosphere, in terms of photoemission, which also requires a small value of W . Further, as pointed out earlier, Mendis et al [2004] provided an explanation for the observation of nanometer‐sized, positively charged grains observed in the night side tropical mesosphere [ Gelinas et al , 1998], in terms of recondensation of the positively charged spray from an ablating positively charged micrometeoroid traversing that region. This too required a low value of W ≈ 2 eV.…”
Section: Resultsmentioning
confidence: 71%
“…Also while these values correspond to ''clean'' metallic oxides, even lower values of W could be achieved for many materials, if their surfaces were contaminated by electronegative species such as oxygen [Jenkins and Trodden, 1965], as would be expected for micrometeoroids traversing the upper atmosphere. It was also pointed out that values of W ranging from $2.3 eV to lower, were used by several authors attempting to explain positive grain potentials observed in the summer polar mesosphere, in terms of photoemission, which also requires a small value of W. Further, as pointed out earlier, Mendis et al [2004] provided an explanation for the observation of nanometer-sized, positively charged grains observed in the night side tropical mesosphere [Gelinas et al, 1998], in terms of recondensation of the positively charged spray from an ablating positively charged micrometeoroid traversing that region. This too required a low value of W % 2 eV.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…All these authors, of course, assume that this dust, which was observed when the sun was just 10 above the horizon was positively charged due to photoemission. We, (Mendis et al, 2004) have very recently proposed that the nanometer sized dust observed in night-side tropical mesosphere (Gelinas et al, 1998) was associated with recondensation of the ablate of positively charged micrometeoroids having W ¼ 2 eV; the positive charge being due to thermionic emission. In the numerical results we present we confine ourselves to the initial micrometeoroid size of 100 mm, which corresponds to the inferred median value.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Some observational consequences of these processes have already been discussed. In particular, the role of thermionic emission has been invoked (Mendis et al 2004) to explain the unexpected observation of a multi-layered region of fine dust (a positively charged thick upper layer and a negatively charged thin lower layer) near the tropical mesopause 30 min after local astronomical sunset (Gelinas et al 1998). Also, a natural explanation for the observed difference between radar 'trail echoes' (associated with the electron trail left behind by the moving micrometeoroid) and the co-moving 'head echo' has been offered in terms of a thermionic electron sheath around the heated micrometeoroid (Mendis et al 2005).…”
Section: Discussionmentioning
confidence: 99%